(untitled) (Applied Biological Research, 2014)
Stone fruit crops, comprising of apricot, cherry, peach, plum and nectarines, are widely distributed throughout the temperate and sub-temperate regions of world. In India, they are grown in Himalayan mountainous region mainly in the states of Jammu & Kashmir, Himachal Pradesh and Utarakhand. In Jammu & Kashmir state the stone fruit crops are grown on 17,415 ha with annual production of 39,160 metric tonnes (Anonymous, 2012). In July-August 2013, during a routine disease survey of fruit orchards, the leaves of apricot, cherry, peach and plum were found affected by an unusual disease. The leaves of infected plants developed rusty brown pustules which manifested as small circular to angular pale yellow spots on both the leaf surfaces. The spots on lower leaf surface developed typical cinnamon rusty brown pustules (sori) of urediniospores. Black teliospores developed in late season among the cinnamon rusty brown urediniospores. The leaves bearing rust pustules turned yellow or red and resulted in severe leaf defoliation (Plate 1a-c). The twig infection although inconspicuous appeared as light water-soaked swellings bearing the urediniospores of fungus.